Analisis Strategi dan Pengembangan Usaha UMKM Pembudidayaan Ikan Lele dan Patin di Patumbak - Ratna Sari Dewi; Hardiansyah Hardiansyah; Aditya Nur Kholis; Sultan Hibrizhi; Rio Mahesa Wahyu Pratama; Agus Syahputra Purba (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting the national economy, particularly in the fisheries sector. This study was conducted through a direct interview with a fish farming MSME, GG Sawah Farm, managed by Legiono. The purpose was to explore the dynamics of catfish and pangasius farming businesses, including business history, capital needs, marketing strategies, and the challenges faced. The findings reveal that despite its promising economic potential, the business encounters various obstacles such as feed costs, seed availability, and climate changes. However, through innovations such as the use of alternative feed, social media marketing, and product diversification into the frozen food sector, the enterprise has managed to survive and grow. This study recommends improving production efficiency, increasing financial support, and encouraging collaboration with stakeholders to enhance the sustainability and development of small-scale fish farming businesses in Indonesia.